Defoliants and Desiccants - Frederick M. Fishel (EDIS)
Revised! PI-101, a 2-page fact sheet by Frederick M. Fishel, discusses the meaning of the terms “defoliant and desiccant,” describes uses of defoliants and desiccants, and provides a listing of these products registered for use in Florida. Published by the UF Department of Agronomy, February 2009.